"Confusion Of Life" In Few Late Poems Of Sylvia Plath - Sharma, Til Kumari; Yadav, Uma Shankar (A Bi-annual South Asian Journal of Research & Innovation, 2023)
This article has endeoureved to show the confusion of life in the few poems of Sylvia Plath. Her late poems have shown the pessimistic life and the hopeless situation. Sylvia Plath as the notable author of America has presented the woman confusion in society with restriction of father and husband. Her keen interest in art has built her the immense figure of American literature. She is well known figure of American literature after World War Second. Her historical background shows the bafflement of life. Her family movement to another place of America after the death of her father shows the economic crisis of life. Her scholarship has helped her to join in Smith College. She had finished her B.A when she married to Ted Hughes. Her deep love to Ted Hughes brings the confusion in life that has invited death with suicide. Anyway, this article clearly depicts the life and barriers of human destiny. The faithless husband makes her life unhappy and sad. This article has maintained the pain and suffering of Plath. The Post War Period in which people loss hope and aspiration to live the life is shown in this research paper. Her later poems show the total meaningless life and her desire to do suicide. Sylvia Plath has been suffered by male society in which she is tortured by father and husband. The restriction by father and husband is shown in her poem Daddy. She has demonstrated the extreme hard life in her late poems Lady Lazarus and Daddy. She was really pessimistic figure in America and she became more famous after her death. Daddy and Lady Lazarus were published after her death. These poems are composed after the separation with her husband.